PENGEMBANGAN BAHAN AJAR KONTEKSTUAL KITAB RIYADUSH SHALIHIN UNTUK MENINGKATKAN KARAKTER ISLAMI SISWA DI MADRASAH DINIYAH ‘ULYA PONDOK PESANTREN MODERN MUHAMMADIYAH LAMONGAN - Fazlinawati, Nur; Ikrom, Abdu Dzil Jalali Wal (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
The fundamental goal of education is the implementation of educational values. The problem of successful implementation is influenced by many things, one of which is teaching materials. At Madrasah Diniyah 'Ulya, the Muhammadiyah Lamongan Modern Islamic Boarding School, one of the hadith books Riyadhush Shalihin is taught. The book of hadith is famous for its moral education. To support the objectives of this implementation, efforts are being made to develop contextual teaching materials for the book Riyadhush Shalihin . This research uses research and development methods. Data collection techniques use interviews, questionnaires, participant observation, and documentation. Data analysis uses descriptive analytics. Data validation by media experts and material experts with product follow-up by testing the first product and the product after revision. The results of this research show the results of validation of teaching material development products by material experts with a percentage of 83% and 94% by media expert. The first trial stage showed students' understanding results with an average of 82 and the second trial obtained an average of 93. The results related to the development of teaching materials in the first trial showed a score of 38.13 with the criteria tending to be good. Meanwhile, trial II showed a score of 40 with good criteria. Tujuan fundamental dari pendidikan adalah implementasi dari nilai-nilai pendidikan. Problem dari keberhasilan implementasi ini dipengaruhi dari banyak hal, salah satunya adalah bahan ajar. Di Madrasah Diniyah ‘Ulya Pondok Pesantren Modern Muhammadiyah Lamongan diajarkan salah satu kitab hadis Riyadhush Shalihin . Kitab hadis yang terkenal dengan pendidikan akhlaknya. Untuk mendukung tujuan dari implementasi ini diupayakan untuk melakukan pengembangan bahan ajar kontekstual kitab Riyadhush Shalihin . Penelitian ini menggunakan metode research and development. Teknik pengumpulan data menggunakan wawancara, kuisioner, observasi partisipan, dan dokumentasi. Analisis data menggunakan deskriptif analitik. Validasi data oleh ahli media dan ahli materi dengan tindak lanjut produk dengan uji coba produk pertama dan produk setelah direvisi. Hasil dari penelitian ini menunjukkan hasil validasi terhadap produk pengembangan bahan ajar oleh ahli materi dengan persentase 83%, dan 94% dari validator ahli media. Tahap uji coba pertama menujukkan hasil pemahaman peserta didik dengan rata-rata 82 dan uji coba kedua diperoleh rata-rata 93. Adapun hasil terkait pengembangan bahan ajar pada uji coba I menujukkan nilai 38.13 dengan kriteria cenderung baik. Adapun pada uji coba II menunjukkan nilai 40 dengan kriteria baik.